Malaria transmission, insecticide resistance and efficacy of insecticide-treated nets in Belabo and Ouami, two localities of the East Region of Cameroon - Paulette Ndjeunia-Mbiakop; Idriss Nasser Ngangue-Siewe; Abdou Talipouo; Arnold Princewil Chi Nji; Roland Bamou; Joel Djoufounna; Jeannette Tombi; Christophe Antonio-Nkondjio (Current Research in Parasitology and Vector-Borne Diseases)
The East Region of Cameroon has over 150 malaria cases per 1000 inhabitants per year. Factors contributing to this high malaria prevalence are not well understood. This study assessed the bionomics of vectors involved in malaria transmission, their susceptibility to insecticides, and the efficacy of insecticide-treated nets. Entomological studies were conducted twice yearly in Belabo and Ouami from 2021 to 2023 using both human landing catches and CDC light traps to collect adult mosquitoes. Anopheline species were separated using morphological identification keys and Anopheles gambiae (s.l.) were molecularly identified to species. Plasmodium falciparum presence was detected by ELISA. Susceptibility of 3–5-day-old An. gambiae (s.l.) to deltamethrin, permethrin, malathion and bendiocarb was assessed. A WHO cone test was performed to assess bednet efficacy against mosquitoes. Out of 7634 mosquitoes collected, 47.44% were anophelines. Anopheles gambiae (s.l.) was the most abundant species, followed by An. ziemanni, An. funestus and An. paludis in both localities. The mosquito biting rate was similar in Belabo and Ouami. Both Anopheles gambiae (s.l.) and An. funestus were infected with P. falciparum at Ouami but only An. gambiae (s.l.) was infected at Belabo. Anopheles gambiae (s.l.) was less susceptible to both deltamethrin and permethrin. None of the 48 bednets tested were effective against field populations of Anopheles gambiae (s.l.) in both sites. High malaria transmission associated with high pyrethroid resistance rate was recorded in vectors from the East Region of Cameroon supporting the high endemicity of malaria in the area.